LIFE QUALITY IN IRAQI CHILDREN AND ADOLESCENTS LIVING IN AREAS OF ARMED CONFLICT - Pavlova, Iuliia; Vynogradskyi, Bogdan; Abdulkareem Jassim Al Ubaidi, Ali (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The aim of the paper was to analyze the quality of life (QL) of Iraqi children and adolescents, and identify which aspects of functioning had the greatest impact on the overall assessment of the well-being in this population group. Participants were healthy children aged 5–18 years (n=150, 50% females) who studied in Baghdad schools. QL was assessed using PedsQL questionnaire by four scales – physical (PF), emotional (EF), social (SF), and school functioning (SchF). Samples were compared using the Kruskal–Wallis test. An exploratory factor analysis was performed to understand the structure of QL. The QL of Iraqi children was moderate. The highest level of PF, SF, and SchF had persons aged 13–18 years (p<0.05). Females had a higher level of QL (p<0.05), regardless of age. It was established that the data was convenient for factor analysis (KMO=0.753, χ2=110.047; p=0.000). The results showed that the varimax method presents the best fit. Factor analysis supported the 2-component model that explained 73.86% of the total variance.